2014
DOI: 10.1115/1.4027274
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Emission Comparison of Spark Ignition Direct Injection (SIDI) and Port Fuel Injection (PFI) Operation of a Boosted Gasoline Engine

Abstract: Spark ignition direct injection (SIDI) gasoline engines, especially in downsized boosted engine platforms, are increasing their market share relative to port fuel injection (PFI) engines in U.S., European and Chinese vehicles due to better fuel economy by enabling higher compression ratios and higher specific power output. However, particulate matter (PM) emissions from engines are becoming a concern due to adverse human health and environment effects, and more stringent emission standards. To conduct a PM num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…The increase in particulate emissions for GDI engines is likely due to the increased liquid fuel impingement on the combustion chamber walls that can result in liquid fuel that is not totally vaporized and well mixed at the start of combustion. This is turn may cause fuel pool fires generating higher PM emissions (Su et al, 2014;Szybist et al, 2011).…”
Section: Pm Mass Black Carbon and Particle Number Emissionsmentioning
confidence: 99%
“…The increase in particulate emissions for GDI engines is likely due to the increased liquid fuel impingement on the combustion chamber walls that can result in liquid fuel that is not totally vaporized and well mixed at the start of combustion. This is turn may cause fuel pool fires generating higher PM emissions (Su et al, 2014;Szybist et al, 2011).…”
Section: Pm Mass Black Carbon and Particle Number Emissionsmentioning
confidence: 99%
“…Meanwhile, it is widely reported that the particle emission from GDI engines is mainly caused by two types of fuel-rich combustion: (1) locally fuel-rich mixture in the combustion chamber and (2) diffusion-controlled burning of thin films of liquid fuel on the piston or cylinder wall. 8 When the injection timing is advanced, as the distance between injector and piston top surface becomes smaller, it is easy for the fuel spray to touch the piston top surface and wall-wetting phenomenon is obvious. For the injection timing of 270 °CA BTDC, the distance between the injector and piston surface is about 4.8 cm at the beginning of fuel injection, while it is only about 1.5 cm at injection timing of 320 °CA BTDC.…”
Section: Resultsmentioning
confidence: 99%
“…According to a proposal issued by the European Commission, PM number over the New European Driving Cycle (NEDC) for spark ignition direct injection (SIDI) engine powered vehicles will be limited to 6.0E12 particles per kilometer in 2014 and 6.0E11 particles per kilometer in 2017. 8 Given that, how the GDI improves the particulate emission has become a hot area of research in the field of internal combustion engine. 6,9,10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European automotive market, overall share of SIDI vehicles increased sharply beginning in 2008, and is estimated at around 35 % in 2014 [7]. However, It is well known that the PN and particle mass emissions from SIDI engine are higher than that from PFI engine, both at steady-state and driving cycle conditions [8,9]. The increase in particle emissions can be mainly attributed to three types of rich combustion: (1) locally fuel-rich mixture in the combustion chamber, (2) diffusion-controlled burning THERMAL SCIENCE: Year 2018, Vol.…”
Section: Introductionmentioning
confidence: 99%